Cage aquaculture - Beveridge, Malcolm C. M. (Blackwell Pub., 2004)
Since the first edition of this book, 17 years ago, aquaculture has consolidated its position as an important means of producing food and as a contributor to global food security. Cage aquaculture too has continued to expand apace. The third edition of this important, useful and well-received book maintains the original aim of providing a thorough synthesis of information on cages and cage aquaculture practices with data and examples encompassing all major world regions.